Pitch Discrimination: An Independent Factor in Cochlear Implant Performance Outcomes. Issue 9 (October 2015) - Kenway, Bruno; Tam, Yu Chuen; Vanat, Zebunnisa; Harris, Frances; Gray, Roger; Birchall, John; Carlyon, Robert; Axon, Patrick
Abstract : Objective: To assess differences in pitch-ranking ability across a range of speech understanding performance levels and as a function of electrode position. Study Design: An observational study of a cross-section of cochlear implantees. Setting: Tertiary referral center for cochlear implantation. Patients: A total of 22 patients were recruited. All three manufacturers' devices were included (MED-EL, Innsbruck, Austria, n = 10; Advanced Bionics, California, USA, n = 8; and Cochlear, Sydney, Australia, n = 4) and all patients were long-term users (more than 18 months). Twelve of these were poor performers (scores on BKB sentence lists <60%) and 10 were excellent performers (BKB >90%). Intervention: After measurement of threshold and comfort levels, and loudness balancing across the array, all patients underwent thorough pitch-ranking assessments at 80% of comfort levels. Main Outcome Measure: Ability to discriminate pitch across the electrode array, measured by consistency in discrimination of adjacent pairs of electrodes, as well as an assessment of the pitch order across the array using the midpoint comparison task. Results: Within the poor performing group there was wide variability in ability to pitch rank, from no errors, to a complete inability to reliably and consistently differentiate pitch change across the electrode array. Good performers were overall significantly more accurate at pitch ranking ( p = 0.026). Consistent pitch ranking was found to be a significant independent predictor of BKB score, even after adjusting for age. Users of the MED-EL implant experienced significantly more pitch confusions at the apex than at more basal parts of the electrode array. Conclusions: Many cochlear implant users struggle to discriminate pitch effectively. Accurate pitch ranking appears to be an independent predictor of overall outcome. Future work will concentrate on manipulating maps based upon pitch discrimination findings in an attempt to improve speech understanding.